Modular Discontinuous Galerkin Time-Domain Method for General Dispersive Media With Vector Fitting - Amorim, Tiago V. L.; Silva, Elson J.; Moreira, Fernando J. S.; Teixeira, Fernando L. (IEEE journal on multiscale and multiphysics computational techniques, 2025)
We present a novel modular implementation of the discontinuous Galerkin time-domain (DGTD) method to effectively address electromagnetic problems involving general dielectric dispersive media modeled through vector fitting. This approach includes an extended dispersive perfectly matched layer to directly truncate dispersive materials, allowing for the modeling of open domains. The proposed modular and concise DGTD implementation, based on the complex-conjugate pole-residue model, offers flexibility and simplifies the handling of complex medium problems. We apply the formulation to both two-dimensional and three-dimensional canonical scattering problems, demonstrating good agreement with their respective analytical solutions.